Pengaruh Opini Audit, Temuan Audit, dan Tindak Lanjut Hasil Audit terhadap Tingkat Korupsi: Studi Empiris pada Pemerintahan Kabupaten/Kota di Provinsi Sumatera Barat Tahun 2019-2021 - Muhardimansyah, Muhardimansyah; Arza, Fefri Indra (Universitas Negeri Padang, 2025)
This study aims to examine the effect of audit opinion, audit findings, and follow-up on the level of corruption. This type of research is causal associative with a quantitative approach. The population used in this study were all district / city local governments in West Sumatra Province in 2019-2021. The sampling technique in this study used a total sampling technique, there were 57 samples used as research samples. The data used in this study are secondary data obtained from the audit results of the Financial Audit Agency of the Republic of Indonesia, the Central Bureau of Statistics, the West Sumatra High Prosecutor's Office and the official website of each agency. The analysis method used is the multiple regression method. The results showed that audit opinion and audit findings have a positive effect on the level of corruption, follow-up on audit results has a negative effect on the level of corruption. Simultaneously, these variables have a significant influence on the level of corruption.